Rapid scoping review of evidence of outdoor transmission of COVID-19 - Weed, M.; Foad, A. (Canterbury Christ Church University, Centre for Sport, Physical Education & Activity Research (spear), 2020)
This Executive Summary illustrates the findings of a rapid scoping review of evidence of outdoor transmission of COVID-19 commissioned from spear by parkrun. The review was designed to be undertaken rapidly in 15 days and to seek, evaluate and analyse evidence of incidents of outdoor transmission of COVID-19, the settings and environments of such transmission, all relevant circumstances, and the existence or otherwise of any COVID-19 mitigation measures.